On knowing, accounting and the methodological position of Geertz - Mustafa, Hasri; Gaffikin, Michael (2010)
As a consequence of calls to view accounting as a culturally defined discipline Geertz’s work has yielded significant debate among accounting scholars. This review paper argues that Geertz á la interpretive anthropology has been inaccurately characterised by many accounting methodologists. They overlook the theoretical anchoring of Geertzian conceptions of culture schemes - “by isolating its elements”, “internal relationships”, and “in some general way” - that illustrate accounting as a kind of being of knowing – the form of what accounting comes to. This paper traces the implications of this on fundamental consequences for accounting research methodology and establishes a direction to critique from a position from where the claims of Geertz should apparently be held.